O uso de mini implantes ortodônticos como meio de ancoragem para verticalização de molares inferiores: revisão de literatura - Nunes, Marcela Macedo [UNESP] (2018)
The loss of permanent lower molars causes an intabilty in the occlusion, usually related to the extrusion of the antagonist, mesialization of the posterior tooth to space, distalisation of the anterior tooth to space, premature contacts, loss of alveolar bone, among other negative effects. The rehabilitation of these patients by means of fixed partial prosthesis or even by implants is limited due to the lack of space for the insertion of a pontic. For these patients, a careful planning should be done, considering the recovery of space by means of a movement called verticalization of the molars. Orthodontic appliances are required to perform the verticalization. The the biggest challenge for this movement is the local or supporting teeth, and in this context the mini orthodontic implants that expand the clinical possibilities in Orthodontics arise, allowing movements with a large extension, with satisfactory anchorage. The objective of this work is to describe, through a review of the literature, the methods of verticalization of molars with the help of mini orthodontic implants as means of anchorage